Government Internal Control System and Local Government Administration Performance: Evidence from Indonesian Local Governments - Winarna, Jaka; Muhtar, Muhtar; Sutaryo, Sutaryo; Amidjaya, Prihatnolo Gandhi (Public Finance Quarterly, 2021)
This study investigates the effect of local government internal control systems on local government administration performance. We use secondary data from the Ministry of Internal Affairs, Financial and Development Supervisory Agency, Indonesian Statistics Bureau, and respective local government financial statements and websites. We generate a set of panel data from 508 local governments during 2017-2019 with 1524 observations analysed with panel data regression. We evidence that several local governments still have low and medium administration performance in 2017-2019 that has not met the expectation of the Ministry of Internal Affairs as stated in the strategic plan in 2015. Our analysis provides empirical evidence that control environment, risk assessment, and information and communication positively affect local government administration performance. Our result provides implications to the Financial and Development Supervisory Agency to continuously optimise internal control system development programs in Indonesian local governments and the Ministry of Internal Affairs to have higher enforcement of local government administration performance achievement.